Pengaruh Tingkat Pendidikan dan Pengalaman Kerja Terhadap Kinerja Karyawan Pada PT Hasura Mitra Gemilang Tangerang - Siti Riana Tantri; Berlianingsih Kusumawati (Indonesian Journal of Economics Application (IJEA), 2020)
This study aims to analyze the effect of education level and work experience on employee performance at PT. Hasura Mitra Gemilang Tangerang. This research design uses quantitative associative methods and data collection techniques in library research and field research. The data analysis technique used in this study uses multiple linear regression analysis by conducting data quality testing and classical assumption tests. The sampling method uses non-probability sampling techniques. The research sample amounted to 83 respondents. The results of the study prove that the level of education has a positive and significant effect on employee performance, this can be seen from the count (4.324)> t-table (1.664), work experience variables have a positive and significant effect on employee performance, this can be seen from the t-value (14.047)> t-table (1,664) so ​​that it can be stated that partially the level of education and work experience affects the performance of employees at PT. Hasura Mitra Gemilang Tangerang. Based on the results of the F test (simultaneous), the value of F-value (246,935)> F-table (3,11) can be stated that the level of education and work experience together affect the performance of employees at PT. Hasura Mitra Gemilang. While based on the results of the coefficient of determination test obtained Adjusted R Square value 0.861, so it can be stated that the variable level of education and work experience has an effect of 86.1% on employee performance, the remaining 13.9% is influenced by other factors outside the variables used in this research.